The Mediating Effect Of Career Decision Self-Efficacy On Self-Development System Adoption Intentions Among Higher Education Teachers In Liaoning - Wang, Dan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose of the Study: Against the digital era backdrop, this study addresses career development challenges of higher vocational college teachers in Liaoning, China, exploring how Technology Acceptance (TA), Organizational Support (OS), Career Adaptability (CA), Career Planning (CP), and Achievement Motivation (AM) influence Self-Development System (SDS) usage intention—with Career Decision Self-Efficacy (CDSE) as the mediator—and integrates SCCT, TAM, and SDT to inform teachers’ digital career development.Research Methodology: Adopting a mixed-methods approach, it surveyed 480 teachers from 4 local vocational colleges via stratified random sampling (400 valid questionnaires, 92% validity), using SPSS 26.0, AMOS 24.0 and other analyses, while interviewing 30 teachers to supplement quantitative data. Results: the structural model fits well (χ²/df=2.085, CFI=0.93, RMSEA=0.052); CDSE partially mediates TA/OS/CA/CP-SDS intention (p<0.01) and fully mediates AM-SDS intention (p<0.001); CP (β=0.561) and CA (β=0.531) have the strongest total effects on SDS intention (AM the weakest, β=0.310); and males score higher in TA (p=0.032), while teachers ≤25 score lower in CA/CP/CDSE than those 36–45 (p<0.05). Conclusion: CDSE as a key mediator with variable-specific roles, note SDS intention relies more on CP/CA (AM acts via CDSE), emphasize demographic differences (gender, age) requiring targeted interventions, and propose strategies: teachers improve CDSE via goal-setting, colleges build “support-training-incentive” systems, and SDS optimizes usability and integrates practical modules.